Drastic pruning for the production of blackberry in subtropical regions - Campagnolo, Marcelo Angelo; Pio, Rafael (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess different pruning strategies as an alternative for the production of 'Tupy' blackberry in subtropical regions of Brazil. The experiment was carried out in the municipality of Marechal Cândido Rondon, PR, Brazil. The experimental design was a randomized complete block, with eight blocks and three treatments: conventional pruning, drastic summer pruning, and drastic winter pruning. In each plot, consisting of 12 useful plants, phenological and productive data were collected in the 2010/2011 and 2011/2012 production cycles, and the physicochemical quantification of fruits was done in the last production cycle. Drastic summer pruning facilitates the training of blackberry and allows an yield increase of 4,375.6 kg ha-1 in comparison to conventional pruning. Winter drastic pruning greatly decreases plant production.